2016
DOI: 10.1007/s10741-016-9591-2
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and rapid effects of aldosterone: what we know and do not know thus far

Abstract: Aldosterone is the most known mineralocorticoid hormone synthesized by the adrenal cortex. The genomic pathway displayed by aldosterone is attributed to the mineralocorticoid receptor (MR) signaling. Even though the rapid effects displayed by aldosterone are long known, our knowledge regarding the receptor responsible for such event is still poor. It is intense that the debate whether the MR or another receptor-the "unknown receptor"-is the receptor responsible for the rapid effects of aldosterone. Recently, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 276 publications
0
41
0
4
Order By: Relevance
“…However, p53 activation could also be regulated by a wide variety of posttranslational modifications such as phosphorylation, acetylation, and ubiquitination in addition to its expression level (36). Moreover, the mechanisms of action of aldosterone may be either genomic or nongenomic effects (14). Our previous study showed that aldosterone-induced podocyte apoptosis was inhibited by a mineralocorticoid receptor antagonist, indicating that the response to aldosterone was a classic genomic action (49).…”
Section: Discussionmentioning
confidence: 99%
“…However, p53 activation could also be regulated by a wide variety of posttranslational modifications such as phosphorylation, acetylation, and ubiquitination in addition to its expression level (36). Moreover, the mechanisms of action of aldosterone may be either genomic or nongenomic effects (14). Our previous study showed that aldosterone-induced podocyte apoptosis was inhibited by a mineralocorticoid receptor antagonist, indicating that the response to aldosterone was a classic genomic action (49).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are required to confirm whether atrasentan has additional renal protective effects on top of the RAS blockades and SGLT2 inhibitors, the new standard care for DKD patients. Mineralocorticoid receptor antagonists (MRA) exert an antifibrotic and anti-inflammatory effect on the kidneys and other target organs like the heart and vessels [77]. Due to significant side effects associated with the first- (spironolactone) and second- (eplerenone) generation MRA, new MRA such as apararenone (also called MT-3995), esaxerenone, and finerenone have a relatively low risk of hyperkalemia.…”
Section: Challenges and Opportunities In Developing New Therapies Formentioning
confidence: 99%
“…Exactly how spironolactone interferes with cAMP signaling is not known. An interplay between cAMP and the mineralocorticoid receptor signaling pathways has been described, please see review and references herein [18].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, different models, read-outs, methods, doses of aldosterone and study designs have been used in the context of spironolactone, aldosterone and the inner ear which may explain some of the contradictory results. One should have in mind that aldosterone is believed to act via the mineralocorticoid receptor as well as via cell surface receptors [18] whereas spironolactone is believed to antagonize the effects induced by the mineralocorticoid receptor only. The exact arrangement and levels of key targets for aldosterone such as the amiloride sensitive Na þ transporter ENaC, NCC and the NaK-ATPase in the inner ear presumably contribute to the impact of altered aldosterone level in different contexts in one or the other direction [19].…”
Section: Discussionmentioning
confidence: 99%